MODERN METHODS OF FORMING THE COMPETENCE OF WRITTEN EXPRESSION OF OWN OPINIONS IN LITERATURE LESSONS (Multidisciplinary Journal of Science and Technology, 2023)
ABSTRACTThe article outlines strategies aimed at fostering students' competency in articulating their thoughts in writing during literature classes. It delineates methodologies for shaping creative written pieces, considering factors such as the artistic quality of the studied work, the richness of language imagery, and proficiency in using emotional and expressive tools. Literary-speech competencies surpass mere narration or description; they encompass the realm of literary-critical observation. Essays composed in literature classes center on work analysis. To stimulate student creativity, particularly with home essays, specific guidelines for their organization have been formulated.